Existence of positive solutions for singular higher-order fractional differential equations with infinite-point boundary conditions - Guo, L.; Liu, Lishan; Wu, Yong Hong (SpringerOpen, 2016)
In this paper, we consider a class of singular fractional differential equations with infinite-point boundary conditions. The fractional orders are involved in the nonlinearity of the boundary value problem, and the nonlinearity is allowed to be singular with respect to not only the time variable but also to the space variable. Firstly, we give Green’s function and establish its properties. Then, we utilize the sequential technique and regularization to investigate the existence of positive solutions. Finally, we give an example of application of our result.